A Novel Blockade CD47 Antibody With Therapeutic Potential for Cancer - Lin, Fangzhen; Xiong, Mengshang; Hao, Wei; Song, Yuewen; Liu, Ruoqi; Yang, Yuanyuan; Yuan, Xiangfei; Fan, Dongmei; Zhang, Yizi; Hao, Mu; Ye, Zhou; Lu, Yang; et al. (Frontiers in Oncology, 2021)
Macrophages as components of the innate immune system plays a critical role in anti-tumor responses. Strategies for targeting CD47 are becoming a hot spot of cancer therapy. The expression of CD47 is exercised by macrophages to make a distinction between “self” or “non-self”. Anti-CD47 antibody blockade the interaction between macrophage signal regulatory protein-α (SIRPα) and tumor surface CD47. In this study, we reported and assessed a novel anti-CD47 blocking antibody named 2C8, which exhibited high affinity and tremendous anticancer effects. More concretely, 2C8 significantly induced macrophages including pro-tumorigenic subtype M2 macrophages killing tumor cell in vitro, revealed more effective than commercially available anti-CD47 mAb B6H12.2. In vivo, 2C8 controlled tumor growth and extended survival of xenograft mice. The anti-tumor ability of 2C8 might be applicable to many other cancers. The generation of novel CD47 antibody contributes to consolidate clinical interest in targeting macrophages for the treatment of malignancy. Moreover, as a supplement therapy when patients resistant or refractory to other checkpoint therapies or relapsing after such treatments.